PERSEPSI AUDITOR TERHADAP PENERAPAN AUDIT FORENSIK DALAM MENDETEKSI KECURANGAN PENYAJIAN LAPORAN KEUANGAN (Survey Pada Kantor Perwakilan BPKP Jawa Timur) - Nur Shodiq; Anita Carolina; Yudhanta Sambharakhresna (JAFFA, 2013)
This  study  aims  to  analyze  the  differences  in  the  perception  of  Auditor Finance and Development Supervisory Agency (BPKP) to application of the forensic audit to detect fraudulent statement. Distinguished by differences in the perception of the scope of work, educational background and work experience.This  study  used  quantitative  approach  and  a  comparative  study  that compared the three samples but has only one independent variable, namely the perception of auditor BPKP to the application of the forensic audit to detect fraudulent statement. This study is an empirical study with purposive sampling techniques in data collection. Data obtained by distributing 105 questionnaires in BPKP East Java. T he hypothesis test used Samples Free Kruskal-Wallis.The results of hypothesis test show that: 1) there is no significant difference in the perception of auditor BPKP based on scope of work, 2) which is based educational background shows that  there  is  no  significant  difference  in  the perception   of   auditor   BPKP,  3)  while  based  on  the  results  show  the  work experience there are differences in the perception of auditor significant BPKP to the adoption of a forensic audit to detect fraudulent statement.